A calculus problem by A Former Brilliant Member

Calculus Level 3

Evaluate.

x 2 ( 5 + 2 x 3 ) 8 d x \large \int x^2(5+2x^3)^8dx

Note: C C is the constant of integration

1 9 ( 6 x 2 ) 9 + C \dfrac{1}{9}(6x^2)^9 + C 1 9 ( 5 + 2 x 3 ) 9 + C \dfrac{1}{9}(5+2x^3)^9 + C 1 54 ( 5 + 2 x 3 ) 9 + C \dfrac{1}{54}(5+2x^3)^9 + C 1 54 ( 6 x 2 ) 9 + C \dfrac{1}{54}(6x^2)^9 + C

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Theorem: [ g ( x ) ] n [ g ( x ) d x ] = [ g ( x ) ] n + 1 n + 1 + c \int [g(x)]^n[g'(x)dx]=\dfrac{[g(x)]^{n+1}}{n+1}+c , where n 1 n≠-1

x 2 ( 5 + 2 x 3 ) 8 d x \int x^2(5+2x^3)^8dx

Observed that if g ( x ) = 5 + 2 x 3 g(x)=5+2x^3 then g ( x ) d x = 6 x 2 d x g'(x)dx=6x^2dx

Because

x 2 ( 5 + 2 x 3 ) 8 d x = ( 5 + 2 x 3 ) 8 ( x 2 d x ) \int x^2(5+2x^3)^8dx=\int (5+2x^3)^8(x^2dx)

we need a factor of 6 6 to go with x 2 x^2 to give g ( x ) d x g'(x)dx . Therefore, we write

( 5 + 2 x 3 ) 8 ( x 2 d x ) = 1 6 ( 5 + 2 x 3 ) 8 ( 6 x 2 d x ) \int (5+2x^3)^8(x^2dx)=\dfrac{1}{6} \int (5+2x^3)^8(6x^2dx)

Applying the theorem above with g ( x ) g(x) and g ( x ) d x g'(x)dx given, we get

1 6 ( 5 + 2 x 3 ) 8 ( 6 x 2 d x ) = 1 6 ( 5 + 2 x 3 ) 9 9 + C = \dfrac{1}{6} \int (5+2x^3)^8(6x^2dx)=\dfrac{1}{6} \dfrac{(5+2x^3)^9}{9}+C= 1 54 ( 5 + 2 x 3 ) 9 + C \color{#D61F06}\boxed{\dfrac{1}{54}(5+2x^3)^9+C}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...